Growth Mindset and Job Crafting: A Trait Activation Perspective with Job Autonomy as Moderator - Tao Yu; Lidong He; Hu Ying; Jie Liu; Yuzhen Wu; Yun Wang; Xiaofu Pan (Behavioral Sciences)
Job crafting benefits both employees and organizations by enhancing employees’ health, well-being, and performance. Therefore, it is crucial to investigate the individual factors that encourage job crafting and the conditions under which they operate. Based on Trait Activation Theory, this study examined the relationship between employees’ growth mindset and job crafting, as well as the moderating effect of job autonomy on this relationship. In Study 1, we conducted a situational experiment with 180 participants, manipulating growth vs. fixed mindset and high vs. low job autonomy. In Study 2, we surveyed 236 participants over three waves, collecting demographic data and growth mindset at T1, job autonomy at T2 (one month later), and job crafting at T3 (two months later). Results from Study 1 indicated that growth mindset significantly impacted job crafting, moderated by job autonomy. Study 2 confirmed this positive effect of growth mindset on job crafting and revealed a significant positive interaction between growth mindset and job autonomy. These findings suggest that employees with a growth mindset engage more in job crafting, with this relationship strengthened under conditions of high job autonomy. This study highlights job autonomy as a situational cue that activates employees’ growth mindset, enhancing proactive job crafting behaviors. This research advances the literature on positive work behaviors by establishing growth mindset as a direct antecedent and illustrating the moderating role of job autonomy, thereby enriching the understanding of conditions that foster a positive workplace environment.